Registros centralizados de patologías cognitivas - Di Nella , Yago; Bartoloni , Leonardo; Russo , María Julieta; Sola , Miriam; Calvillo , Lidia; Negro , Lorena; Venesio , Sofía; Paz, Andrea; Melcon , Carlos; Del Mónaco , Rodrigo; Melcon , Mario; Allegri , Ricardo (Revista Argentina de Salud Pública, 2012)
Registros centralizados de patologías cognitivas